One‐Pot Hydrothermal Synthesis for a Manganese Oxide Molecular Sieve for Application in Mercury Removal in Chloride‐Free Flue Gas. Issue 12 (28th March 2022) - Han, Jun; Shan, Weiwei; Zhao, Bo; Tian, Chong; Ma, Junwei; Zhang, Qiang; Qin, Linbo; Chen, Wangsheng
Abstract: OMS‐2 (manganese oxide octahedral molecular sieve) were prepared by one pot hydrothermal method under different temperatures in this work, and their performances of oxidizing elemental mercury (Hg 0 ) in the flue gas derived from coal combustion were evaluated. Moreover, the effects of the reaction temperature and flue gas component on Hg 0 oxidation ability of these catalysts were also investigated. It is found that OMS‐2 catalysts have an excellent mercury oxidizing ability under 100–200 °C, and 94 % Hg 0 oxidation efficiency could be achieved by catalyst prepared under 120 °C (OMS‐2‐H120) in the chlorine free flue gas. The process of elemental mercury oxidation over OMS‐2‐H120 by O2 is found to follow Mars‐Maessen mechanism based on the XPS and FTIR analysis of the fresh and spent catalysts. NO is the precursors of the active species such as NO −, NO2, which is benefit to improve Hg 0 oxidation ability of OMS‐2‐H120. SO2 have a negative effect on Hg 0 oxidation over OMS‐2‐H120 while water vapor exhibits nearly no influence. Abstract : OMS‐2‐H120 catalyst was prepared using one‐pot hydrothermal synthesis method, which achieved 94 % Hg 0 oxidation efficiency in chloride‐free flue gas. O2 facilitated elemental mercury removal, while NO improved the mercury oxidation ability of the catalyst by generating active species such as NO −, NO2, and NO2 − . SO2 had a negative effect on Hg 0 oxidation on OMS‐2‐H120, while water vapor had almost no effect.